2018
DOI: 10.30560/hssr.v1n1p46
|View full text |Cite
|
Sign up to set email alerts
|

Forced Displacement and the Plight of Internally Displaced Persons in Northeast Nigeria

Abstract: Since the end of the Cold War, the phenomenon of forced displacement gained more global attention. Forced displacement involves the involuntary movement of people from their habitual place of residence to a location within their country of nationality; or across an internationally recognised border. This situation in most cases exposes the displaced people to some vulnerabilities. Among other classes of displaced people, the most notable groups of concern are refugees and internally displaced persons (IDPs). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…This study found that the major non-health challenges of the IDPs are lack of food and clothing, frequent illness due to lack of drugs and no doctors to attend to their health need. These findings are in line with the reports of previous studies that enumerated the challenges of IPDs in Nigeria as "lack of education, shelter, food, health care, and potable water" (USAID, 2016;Obaji & Alobo, 2016;UNPF, 2016;Akuto, 2017;Mohammed, 2017;Gwadabe et al, 2018;Olanrewaju et al, 2018Olanrewaju et al, , 2019DTM Nigeria, 2019;Opara, 2019;Prince et al, 2019). A similar challenge was also reported in Colombia (Hines & Balletto, 2002), in Ethiopia (Eweka & Olusegun, 2016), in Iraq (REACH, 2016), in Kachin (Nau, 2014), in Angola, Somalia, Indonesia, Kosovo, Afghanistan, the Democratic Republic of Congo (DRC), Colombia, Liberia, Eritrea, and Sudan (Borton et al, 2005).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study found that the major non-health challenges of the IDPs are lack of food and clothing, frequent illness due to lack of drugs and no doctors to attend to their health need. These findings are in line with the reports of previous studies that enumerated the challenges of IPDs in Nigeria as "lack of education, shelter, food, health care, and potable water" (USAID, 2016;Obaji & Alobo, 2016;UNPF, 2016;Akuto, 2017;Mohammed, 2017;Gwadabe et al, 2018;Olanrewaju et al, 2018Olanrewaju et al, , 2019DTM Nigeria, 2019;Opara, 2019;Prince et al, 2019). A similar challenge was also reported in Colombia (Hines & Balletto, 2002), in Ethiopia (Eweka & Olusegun, 2016), in Iraq (REACH, 2016), in Kachin (Nau, 2014), in Angola, Somalia, Indonesia, Kosovo, Afghanistan, the Democratic Republic of Congo (DRC), Colombia, Liberia, Eritrea, and Sudan (Borton et al, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…The lack of drugs can be attributed to the many health facilities that have been destroyed through bomb blast or suicide attacks on health facilities in this region. Previous studies have reported malaria, fever, and diarrhoea as the major health challenge in IDP camps (Eweka & Olusegun, 2016;UNPF, 2016;Gwadabe et al, 2018;WHO, 2018;DTM Nigeria, 2019) while some have documented a high rate of skin infections (Özcebe et al, 2014;Elfaituri, 2016;USAID, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Migration in this paper is more related to forced displacements than to any other form of migration. Forced migration has been defined as the movement of people, displaced by conflict, natural or environmental disasters, or the consequences of the previous factors such as famine [15]. The intensification of attacks by non-state armed groups in northeast Nigeria since 2015 has resulted in prolonged insecurity, exacerbating the plight of vulnerable civilians, and triggered waves of forced displacement as well as violations of human rights [33].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Boko Haram insurgency and the counter-insurgency by the Nigerian security forces is the primary cause of forced displacements in Nigeria [15]. Since 2009, the crisis caused by this conflict has forced more than two million people to flee for safety within Nigeria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation